أثر الرشاقة الاستراتيجية في تعزيز التميز التسويقي في فنادق الخمس نجوم بولاية عنابة - زرفة ،رؤوف; بوناب ،محمد (جامعة الوادي University of Eloued, 2025)
This study aimed to analyze the role of strategic agility and its contribution on enhancing marketing excellence in five-star hotels in Annaba. To achieve this objective, the descriptive-analytical approach was adopted, the study relied on a questionnaire distributed to a sample of 43 administrative employees, the data collected was analyzed using SPSS v25. The study revealed a statistically significant positive correlation between strategic agility with its dimensions (strategic sensitivity, resource fluidity, leadership unity, and vision clarity) and marketing excellence in the Sheraton and Seybousse hotels in Annaba.
The Impact of Strategic Agility on Enhancing Marketing Excellence in Five-Star Hotels in Annaba
مقال
Keywords: الرشاقة الاستراتيجية; التميز التسويقي; فندق سيبوس الدولي; فندق شيراتون; Strategic Agility; Marketing Excellence; Seybousse Hotel; Sheraton Hotel.